2017
DOI: 10.1109/toh.2017.2704603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Waveform on Tactile Perception by Electrovibration Displayed on Touch Screens

Abstract: In this study, we investigated the effect of input voltage waveform on our haptic perception of electrovibration on touch screens. Through psychophysical experiments performed with eight subjects, we first measured the detection thresholds of electrovibration stimuli generated by sinusoidal and square voltages at various fundamental frequencies. We observed that the subjects were more sensitive to stimuli generated by square wave voltage than sinusoidal one for frequencies lower than 60 Hz. Using Matlab simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 52 publications
5
84
2
Order By: Relevance
“…However, the subjects were not able to perceive the sinusoidal wave at 5 Hz. Varder et al reported that the simulated input voltage applied to the skin decreased significantly under low frequency sinusoidal waveform conditions and that the resulting electrostatic force also decreased significantly [38]. It is believed that the decrease in electrostatic force under low frequency condition resulted in a low rate of perception and this rate also decreased with increase in the frequency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the subjects were not able to perceive the sinusoidal wave at 5 Hz. Varder et al reported that the simulated input voltage applied to the skin decreased significantly under low frequency sinusoidal waveform conditions and that the resulting electrostatic force also decreased significantly [38]. It is believed that the decrease in electrostatic force under low frequency condition resulted in a low rate of perception and this rate also decreased with increase in the frequency.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the subjects answered with these words, which indicated a smooth surface. On the other hand, the response for the tactile sensation of pulse voltage and triangle waveform was either “bumpy” or “rough.” In the case of pulse voltage, the amplitude of the calculated electrostatic force was higher than that of the sinusoidal voltage and was edgy in nature [38]. This trend resulted in the above answers for the tactile sensation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrical attraction between a charged surface and a human finger was discovered by Johnsen and Rahbek. In 1953 Mallinckrodt et al [3] applied an alternating voltage to insulated metal electrodes and observed an alternating electrostatic force that periodically attract and release the finger from the surface; this is now denoted electrovibration [4][5][6][7], and forms the basis for electroadhesion based haptic devices such as touchscreens and tactile displays. For these applications, tactile sensations are produced by the application of a voltage to the conductive layer of an insulated haptic device such as a touchscreen, inducing electroadhesive forces between the device and the approached user finger.…”
Section: Introductionmentioning
confidence: 99%
“…For these applications, tactile sensations are produced by the application of a voltage to the conductive layer of an insulated haptic device such as a touchscreen, inducing electroadhesive forces between the device and the approached user finger. If the applied electric voltage is modulated in time the friction force acting on the finger will generate sensorial experiences [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%